PENGUATAN PERENCANAAN PEMBANGUNAN DESA KUIN KECIL, KECAMATAN ALUH-ALUH, KABUPATEN BANJAR KALIMANTAN SELATAN TAHUN ANGGARAN 2021 - Syafril Djaelani; Muhammad Fahmi; Mohdari Mohdari; Neti Rosiana Fadilah; Yuliani Yuliani; Boy Sapto Suryo; Wiszda Asma (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2022)
The village is the smallest form of regional autonomy that is able to realize village independence with a set of village government tools such as village funds for village empowerment and progress. In the implementation of strengthening the development of Kuin Kecil village, Aluh-Aluh District, Banjar Regency, a village meeting was held on the use of village fund allocations. Community service is carried out by the method of presentation and discussion followed by questions and answers regarding village funds that will be used for village progress. Community service carried out can bridge the village meeting in the allocation of funds for development according to village development priorities. The allocation of village funds is intended for the administration of village government and community empowerment. Even though there were disagreements between the participants, the deliberations found points of agreement on what areas could be prioritized to be submitted as village assistance funds for the 2021 fiscal year, along with how to make a RT-level budget proposal before it was decided to become a budget at the next village meeting.